Utilization of Recycle Plastic Bottle Caps as Partial Replacement in Mortar - Mahadi, Muhamad Riduan; Ismail, Noorli (Recent Trends in Civil Engineering and Built Environment, 2024)
In consistent with conservation effort, recycling of waste materials and by-products is a partial solution to environmental and ecological issues.  The study is an alternative way to solve the problem above by replacing or reducing the material that commonly use to the recycle material which plastic bottle caps.  The aim of this study is to determine the density, compressive strength and water absorption of cement mortar that containing recycle plastic bottle caps as a sand replacement. This study was focus on develop the cement mortar that containing recycled plastic bottle caps using design replacement which is 0%, 2.5%, 5% and 7.5%. Besides that, water cement ratio that has been used in this research is 0.45. The cement mortar moulded size was 50mm×50mm×50mm were curing for 7 days and 28 days. The laboratory testing will be conducted for density, compressive strength and water absorption. From the analysis that has been done, control mortar is higher than modified mortar that containing plastic bottle caps for the compressive strength test.